The Concept of the Self in Spanish Krausists: Julián Sanz del Río and Francisco Giner de los Ríos. Spirit and Body - De Lucas, Jesús Pedro Payo (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Basing his work on the German master Krause’s philosophy, Sanz and Giner analyse the composition of man, his goodness and finality: his union with humankind or paradise on Earth. Krausism, and specially Giner de los Ríos kept their faith on man’s capacity for perfection and for the achievement of that ideal of humankind. The Spanish Krausist thinkers analyse two basic concepts: God and Man. While the first represents perfection, simplicity and infinity, Man appears as imperfect, finite and complex. This complexity consists of harmony between two elements: Spirit, which unites us with the Creator, and Body with Nature, with the World. Krausism strives for bringing harmony in all these principles which allow the progress of Humankind in its union with God at the end of History. A key concept for our philosophers will be Panentheism or everything in God.